2006
DOI: 10.1016/j.intfin.2004.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of bond market integration between established and accession European Union countries

Abstract: In this paper, we examine the integration of European government bond markets using daily returns over the 1998-2003 period with a set of complementary techniques to assess the time varying level of financial integration. We find evidence of strong contemporaneous and dynamic linkages between Euro zone bond markets with that of Germany. However, there is much weaker evidence outside of the Euro zone for the three accession markets of Czech Republic, Hungary and Poland, and the UK. In general, the degree of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…The finding is also consistent with the time-varying properties of bond correlations in literature which indicates correlations are not consistent across time (for e.g. Cappiello et al (2006), Hunter and Simon (2005), Kim et al (2006) andCiner (2007)). More importantly, the results are consistent with Hansson et al (2009) who, using a sample of bond indices from 11 developed countries and 10 emerging markets, had concluded that although correlations have increased in developed markets over time during [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006], the emerging market debts within both government and corporate bonds still offer lower correlations.…”
Section: International Portfolio Diversificationsupporting
confidence: 88%
See 2 more Smart Citations
“…The finding is also consistent with the time-varying properties of bond correlations in literature which indicates correlations are not consistent across time (for e.g. Cappiello et al (2006), Hunter and Simon (2005), Kim et al (2006) andCiner (2007)). More importantly, the results are consistent with Hansson et al (2009) who, using a sample of bond indices from 11 developed countries and 10 emerging markets, had concluded that although correlations have increased in developed markets over time during [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006], the emerging market debts within both government and corporate bonds still offer lower correlations.…”
Section: International Portfolio Diversificationsupporting
confidence: 88%
“…However, the correlations remain significantly below (absolute) one, indicating that the benefits of international bond diversification have not been eroded over the sample period. Kim et al (2006) use government bond index data and also show that there are time-varying linkages and convergence between the Euro-zone markets and Germany.…”
Section: Portfolio Diversification Of Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher average value indicates a better standing or lower sovereign risk. Sovereign credit ratings are a valuable source of information and have been used as a basis to measure sovereign risk, for example, by Eichengreen et al (2003), Borio 7 and Packer (2004), Kim and Wu (2006), Remolona et al (2008b), andBissoondoyal-Bheenick et al (2011).…”
mentioning
confidence: 99%
“…3. The detachment of long-term equilibrium yields from government bonds in Europe has been widely attributed to a successful convergence of bond yields during the period preceding the euro inception and extending until the recent global financial crisis (Codogno et al, 2003;Côté/Graham, 2004;Kim, et al, 2006), as shown in our Fig. 1a.…”
Section: Literature Survey On Causal Interactions Between Macroecomentioning
confidence: 80%